Agency and Accountability: Promoting Women's Participation in Peacebuilding. Issue 1 (2nd January 2016) - Goetz, Anne Marie; Jenkins, Rob
ABSTRACT: This contribution reviews international policy and practices to engage women in formal peace talks, post-conflict elections, and economic recovery, and finds a combination of factors contributing to poor performance in promoting women's agency. The fact that the privileged category for post-conflict decisions are those groups capable of acting as "spoilers" has tended to exclude women's groups from the categories considered most important to involve in decision making. Exacerbating this exclusion is the reluctance of international decision makers to encourage affirmative action measures in these contexts. This carries through to the minimal-state approach to economic recovery efforts. Provisions are needed to foster and invite women's voice in decision making, and build more active-state approaches to women's livelihood recovery.